2017
DOI: 10.1002/2017gl075213
|View full text |Cite
|
Sign up to set email alerts
|

Strong SH‐to‐Love Wave Scattering off the Southern California Continental Borderland

Abstract: Seismic scattering is commonly observed and results from wave propagation in heterogeneous medium. Yet deterministic characterization of scatterers associated with lateral heterogeneities remains challenging. In this study, we analyze broadband waveforms recorded by the Southern California Seismic Network and observe strongly scattered Love waves following the arrival of teleseismic SH wave. These scattered Love waves travel approximately in the same (azimuthal) direction as the incident SH wave at a dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 40 publications
4
30
0
Order By: Relevance
“…Body-to-surface wave scattering due to surface topography has been studied since the 1960s (Levander, 1990). Converted surface waves similar to our USArray observations have been observed from scattered P waves at the Japan Trench (Maeda et al, 2014), at the Pacific Trench of Mexico (Dominguez et al, 2011), for deep events near Australia (Furumura et al, 1998), and most recently by Yu et al (2017) who reported SH-to Love wave scattering off the Southern California Continental Borderland for deep events in the Fiji region. It is important to be aware of these large-amplitude arrivals cutting across body wave phases, as they could interfere with analyses of direct or converted phases in this part of the wavefield, causing problems for migration, back projection, or attenuation tomography.…”
Section: Introductionsupporting
confidence: 88%
“…Body-to-surface wave scattering due to surface topography has been studied since the 1960s (Levander, 1990). Converted surface waves similar to our USArray observations have been observed from scattered P waves at the Japan Trench (Maeda et al, 2014), at the Pacific Trench of Mexico (Dominguez et al, 2011), for deep events near Australia (Furumura et al, 1998), and most recently by Yu et al (2017) who reported SH-to Love wave scattering off the Southern California Continental Borderland for deep events in the Fiji region. It is important to be aware of these large-amplitude arrivals cutting across body wave phases, as they could interfere with analyses of direct or converted phases in this part of the wavefield, causing problems for migration, back projection, or attenuation tomography.…”
Section: Introductionsupporting
confidence: 88%
“…Figures 10a and 10b). The result is consistent with previous findings in this region (Buehler et al, 2018;Yu et al, 2017a). However, there is no detection of strong scatterers along the continental slope of Atlantic Plains, where topographic gradients are also significant.…”
Section: Sources Of Body-to-surface Wave Scatteringsupporting
confidence: 92%
“…Body-to-surface wave scattering, including both P/SV-to-Rayleigh wave scattering and SH-to-Love wave scattering, has been observed in many locations around the world (e.g. Bannister et al, 1990;Buehler et al, 2018;Furumura et al, 1998;Maeda et al, 2014;Yu et al, 2017a).…”
Section: Observations Of Body-to-surface Wave Scattering Across the Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there is the possibility that this dipping feature is some kind of artifact related to scattering of incoming S waves off the western continental margin, such as the surface-wave scattering observed by Yu et al (2017) and Buehler et al (2018), that is, a feature analogous to a diffraction hyperbola in reflection seismology. To test this idea, we generated a synthetic data set in which we replaced each of our observed seismograms with simple Ricker pulses at offset times from direct S that were derived from the sum of the predicted iasp91 source-to-scatterer time and a scatterer-to-receiver time computed from an assumed surface-wave velocity.…”
Section: Imaging the Farallon Slab?mentioning
confidence: 99%